PENDIDIKAN MORAL DALAM NOVEL SI ANAK BADAI KARYA TERE LIYE DAN RELEVANSINYA SEBAGAI BAHAN AJAR BAHASA INDONESIA DI SMP - Prayitna Putri, Mega (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe moral education in Tere Liye's novel The Child of Storms and its relevance as Indonesian language teaching materials in junior high schools. This research uses a qualitative approach with descriptive methods. The data source for this research is Tere Liye's 318-page novel The Child of Storms, which was published in 2019. The research data was obtained through narration or dialogue between characters that are related to moral education. Collecting research data using document study techniques. Data analysis by doing data reduction, data presentation and verification. The results of this study are that there is moral education including polite behavior, praying and worshiping, sorry and forgiving, helping each other, and caring for others in the novel The Child of Storms by Tere Liye. In addition, there is relevance to the novel Si Anak Storm by Tere Liye as Indonesian language teaching material for class VIII SMP based on Permendikbud Number 37 of 2018 on Basic Competency (KD) 3.12 for knowledge and 4.12 for skills regarding literary review texts.